Metodología de análisis de suelo utilizadas para mejorar la producción del cultivo de banano de exportación (Musa sapientum) - Franco Chica, Irvin Josué (2022)
The purpose of this research work is to analyze the information on the physico-chemical characteristics of the main commercial organic fertilizers in the Babahoyo canton. Organic fertilizers have been recommended for intensive agriculture to improve soil structure and increase nutrient availability and water holding capacity. The benefits of using organic fertilizers such as Fulvin, Seaweed Extract, Bioabor, commercial organic fertilizers in the Babahoyo area, are presented as a healthy means of fertilization for the environment and people, in addition to saving investment costs than chemical fertilizers. In the production different types of organic fertilizers with different physicochemical properties are used, so the more diverse the elements the greater the fertility and biological activity of the soil, the crops grow well and increase the yield.